Influence of flow rate and fiber tension on dynamical, mechanical and acoustical parameters in a synthetic larynx model with integrated fibers - Gühring, Lucia; Tur, Bogac; Semmler, Marion; Schützenberger, Anne; Kniesburges, Stefan (Frontiers in Physiology, 2024)
IntroductionThe human voice is generated by the oscillation of the vocal folds induced by exhalation airflow. Consequently, the characteristics of these oscillations and the primary sound signal are controlled by the longitudinal tension of the vocal folds, the flow rate, and their prephonatoric position. To facilitate independent control of these parameters, a synthetic larynx model was developed, as detailed in a previous publication.MethodsThis study aims to statistically analyze the influence of airflow and fiber tension on phonation characteristics, such as periodicity and symmetry, glottis closure during vocal fold oscillations, as well as tissue elasticity and generated sound. A total of 76 experiments were conducted and statistically analyzed with a systematic variation of flow rate and longitudinal tension within the vocal folds.During these experiments, vocal fold motion, subglottal pressure, and emitted sound were meticulously measured and analyzed.ResultsGroupwise statistical testing identified the flow rate as the main influencing parameter on nearly all phonation characteristics. However, the fundamental frequency, stiffness parameters, and quality parameters of the primary sound signal are predominantly controlled by the longitudinal tension within the vocal folds.DiscussionThe results demonstrated a complex interplay between the flow rate and tension, resulting in different characteristics of the produced sound signal.